The Influence of Brand Awareness and Brand Attitude on Purchase Intention of Riau Malay Woven Products “Puteri Mas” in Bengkalis City - Sari, Rini Arvika; Handayani, Tri; Mawarni, Sri (ABEC Indonesia, 2024)
The purpose of this study is to examine the influence of brand awareness and brand attitude on purchaseintention towards Riau Malay woven products "Puteri Mas" in Bengkalis Regency. Specifically, this research aims todetermine whether brand awareness and brand attitude have a positive and significant effect on purchase intention. Aquantitative approach with a descriptive method was employed, where the research is systematic, planned, and structuredfrom the initial stage to the research design. Data were collected through field surveys using observations, questionnaires,interviews, library research, and documentation. The results from regression analysis show that brand awareness has apositive and significant effect on consumer purchase intention with a coefficient of 0.369 and a significance value of0.032, while brand attitude also has a positive and significant effect with a coefficient of 0.654 and a significance valueof 0.001. Additionally, t-test results confirm the significant impact of both brand awareness and brand attitude onconsumer purchase intention, as indicated by t-values greater than the critical t-table values. Therefore, brand awarenessand brand attitude are crucial factors in influencing the purchase intention of "Puteri Mas" products in Bengkalis City